Judicial Considerations in Granting Interfaith Marriage Applications: A Critical Study of Bandung District Court Decision No. 166/Pdt.P/2022/PN.Bdg within the Framework of Indonesian Marriage Law and Human Rights - Paijar, Pijri (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This article critically examines the Bandung District Court Decision No. 166/Pdt.P/2022/PN.Bdg, which granted an interfaith marriage application despite the absence of explicit legal provisions in Indonesian Marriage Law No. 1 of 1974 and the Compilation of Islamic Law (KHI). Employing a normative juridical method with a library research approach, this study analyzes statutory regulations, judicial practices, and scholarly literature related to marriage law, interfaith unions, and human rights. The findings demonstrate that while Indonesian marriage law emphasizes religious conformity as the legal basis for marriage validity, the court employed judicial activism to justify the registration of interfaith marriages through civil administration, citing the principles of human rights and freedom of religion enshrined in the 1945 Constitution. This decision reflects ongoing legal pluralism in Indonesia, where religious norms and state law often intersect and conflict. The article argues that such judicial practices, though aimed at protecting constitutional rights, create legal uncertainty and social controversy, particularly regarding the legitimacy of interfaith marriages under Islamic law. The contribution of this study lies in highlighting the judicial role in navigating tensions between religious doctrine, constitutional rights, and legal certainty in a plural society, offering insights into the need for harmonization between state and religious laws in Indonesia.